2007
DOI: 10.1002/pca.1014
|View full text |Cite
|
Sign up to set email alerts
|

Primary flavonoids in marigold dye: extraction, structure and involvement in the dyeing process

Abstract: Flavonoids extracted from marigold flowers were investigated for their dyeing potential. Patulitrin (1) and patuletin (2) were isolated and their structures established using NMR and HPLC-MS. These compounds were identified as the main flavonoids present in the dyeing bath. Following the dyeing process, it was demonstrated that aglycone 2 bound more strongly to wool fibres than its glucoside 1. Moreover, analysis focused on 1 and 2 dynamics during plant growth revealed that these components were only found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 24 publications
1
26
0
1
Order By: Relevance
“…Some of them have also been reported to possess anti-UV and anti-microbial properties. As the present trend throughout the world is shifting towards the use of eco-friendly and biodegradable commodities, the demand for natural dyes is increasing day by day (Ali et al, 2009;Guinot et al, 2008).…”
Section: Natural Dyementioning
confidence: 99%
“…Some of them have also been reported to possess anti-UV and anti-microbial properties. As the present trend throughout the world is shifting towards the use of eco-friendly and biodegradable commodities, the demand for natural dyes is increasing day by day (Ali et al, 2009;Guinot et al, 2008).…”
Section: Natural Dyementioning
confidence: 99%
“…The flowers and leaves of Tagetes spp. contain terpenes (PRAKASH et al, 2012) and flavonoids (GUINOT et al, 2008;FAIZI et al, 2011). Free and/ or methoxylated aglycones, such as kaempferol and quercetin (IVANCHEVA; ZDRAVKOVA, 1993), patuletin (GUINOT et al, 2008), quercetagetin (TARPO, 1969), and luteolin and quercetagetin 5-methyl ether (PICCAGLIA et al, 1998) are among the flavonoids that have been isolated and identified, indicating a predominance of this class of compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids patulitrin (patuletin 7-O -glucoside), patuletin, quercetagetin, quercetagetin 7-O -glucoside, luteolin (Bhardwaj et al 1980a ), allopatuletin (3,6,7,3′,4′-pentahydroxy-5-methoxyfl avone) a quercetagetin monomethyl ether (Bhardwaj et al 1980a , b ), and kaempferol) and quercetin-like structures (Ivancheva and Zdravoka 1993 ) (patulitrin (patuletin 7-O -glucoside), patuletin, quercetagetin 7-O -glucoside) and several unknown minor fl avonoids (Guinot et al 2008 ) (pateletin, patulitrin, patuletin cinnamate derivative, patuletin benzoate derivative (Faizi et al 2008 )) were isolated from the fl owers. From the polar extract and fractions of yellow fl owers of Tagetes patula , phenolic compounds (fl avonoids and phenolic acids) were isolated (Faizi et al 2011b ).…”
Section: Nutritive/medicinal Propertiesmentioning
confidence: 98%